BOOK SELECTION BASED ON CHILDREN'S BOOK COVERS: ANALYSIS MULTIMODALITY - Dina Oktafiani; Retno Purwani Sari (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
This study discusses the results of investigations into book selection research based on covers in children aged 3-12 years. The aim is to find out how verbal and visual modes are represented in children's book covers and identify whether they influence children's decisions to buy books. This research focuses on the identification of multimodality texts and visual modes in children's books